MATHEMATICAL MODELING AS A TOOL FOR INTEGRATING NATURAL SCIENCE KNOWLEDGE IN MEDICAL EDUCATION (Uzbekistan Open Conference, 2025)
The article examines the role of mathematical modeling as an effective tool for integrating natural science knowledge into medical education. Special attention is given to the application of models for studying biological and physiological processes such as blood circulation, cell growth, infection spread, and homeostasis regulation. It is shown that the use of mathematical models contributes to the development of systemic and analytical thinking, research competencies, and a deeper understanding of the interconnections between physical, chemical, and biological aspects of human body functioning. The importance of an interdisciplinary approach and digital technologies in implementing modeling in the educational process is emphasized.